Higher Education in Vietnam: United States Agency for International Development Contract in Education, Wisconsin State University-Stevens Point and Republic of Vietnam - Reich, Thomas Charles (Department of History, University of Wisconsin-Stevens Point, 2003)
This thesis explores an important but little known facet of America's war in Vietnam: the U.S. effort to reform the South Vietnamese system of higher education as part of the broader “nation-building” process in the fledgling Republic of Vietnam (RVN). Specifically it examines the interaction among Wisconsin State University-Stevens Point (now the University of Wisconsin Stevens Point), the U.S. Agency for International Development (USAID), and the government of South Vietnam to implement change. The study is based on extensive research in manuscript materials relating to the education mission in the UW-Stevens Point Archives, on oral history interviews with key participants, and on a broad range of other primary and secondary works on Vietnamese history and education, U.S. foreign policy, and America’s general effort to implement nation-building during the Cold War era. After a brief introduction on literature and methodology, the thesis establishes context for the U.S. mission by tracing the history of traditional education in Vietnam from ancient times to the 19th century, stressing the strong influence of Chinese Confucian models. Under French colonial rule in the 19th and 20th centuries, the French revamped higher education along European lines, but skewed it to produce a subordinate Vietnamese administrative class to support French dominance. U.S. involvement with Vietnamese higher education began with the Geneva Accords in 1954, which established an independent RVN, and the onset of the Second Indochina War. In order to bolster South Vietnamese resistance, USAID launched a multifaceted effort to develop education at all levels, contracting with American universities for advice and support. In 1967, USAID recruited President James H. Albertson of WSU-SP to head a group of educators, the original “Wisconsin Team,” to survey and report on colleges and universities in the RVN. Albertson and other members of the team were killed in a plane crash near Da Nang in March, but other WSU-SP personnel completed the survey and later that year the university signed a contract umbrella with USAID and the South Vietnamese government to continue the collaboration. This agreement launched a six-year program by which WSU-SP was the principal institutional adviser to the South Vietnamese system of higher education. On numerous occasions, WSU-SP administrators visited the RVN, submitting detailed reports that suggested changes in curricula, faculty training, student relations, administration, and organization. Moreover, teams of leading South Vietnamese educators frequently visited the U.S., including extended stays on the WSU-SP campus. Not surprisingly, while emphasizing the importance of developing a Vietnamese blueprint, the thrust of the Wisconsin Team’s advice was to restructure public higher education in the RVN on the model of the American state university system. The Vietnamese were impressed by the organizational structure at the institutional and state system levels. They detected a model for growth from the rapid expansion of American higher education, admiring the independent nature of American universities as campus units that afforded educators and students with most necessities. While motivated in part by institutional ambitions, Wisconsin Team members revealed a strong and sincere ideological commitment to exporting American educational values, improving their Vietnamese counterparts, and widening educational opportunities in the RVN. Although limited success occurred in some areas, such as university record keeping and administration, wartime conditions inhibited broad changes, and the mission was eventually overwhelmed by events—the gradual withdrawal of U.S. forces, the “cease-fire” of 1973, the diminished funding for USAID contractual obligations in South Vietnam, and the collapse of the RVN during the North Vietnamese Spring Offensive of 1975. In recent years, indications of the resiliency of mission objectives surfaced with the attempted renewal of educational relations on the part of Vietnamese educators from a unified Vietnam who visited Wisconsin-Stevens Point in 1998.